The Role of Organizational Commitment as a Mediator of the Influence of Situational Leadership on the Turnover Intention of Student Cooperative Members at Udayana University - Suasana, I Gst. A. Kt. Gd.; Anak Agung Gede Suarjaya; Ketut Juliartini; Ida Ayu Putri Laksmidewi Purba (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
Empirical data shows that the participation of students interested in becoming administrators or members of Kopma Unud is still very low. So, higher education which is expected to play a role in fostering learning through the Student Activity Unit (UKM) Kopma Unud organization has not been maximized. The objectives of the study are: a) To explain the influence of organizational commitment on the turnover intention of student cooperative members at Udayana University. b) To explain the influence of organizational commitment on the situational leadership of student cooperative members at Udayana University. c) To explain the influence of situational leadership on the turnover intention of student cooperative members at Udayana University. d) To explain the role of situational leadership as a mediator of the influence of organizational commitment on the turnover intention of student cooperative members at Udayana University. The research respondents were all Unud students who had been and or were currently members of Kopma, with a population of 117 The research sample was saturated, so the sample size was the same as the number of population members. The research data were analyzed using the SmartPLS application.The results of the study illustrate; situational leadership is not significant on turnover intention, situational leadership has a significant effect on organizational commitment, and organizational commitment has a significant effect on turnover intention with a relatively large impact. Other results found that organizational commitment acts as a full mediation of the influence of situational leadership on turnover intention.